Mechanical hemolysis in pediatric patients associated with rapid transfusion and one‐way valve. Issue 5 (1st March 2018) - Gniadek, Thomas J.; Richtsfeld, Martina; Pulkrabek, Shelley; Hansen, Kayla R.; Barnett, Susan L.; Joyner, Nitasha; Kinney, Stephanie; Zantek, Nicole D.; Azakie, Anthony; Cohn, Claudia S.
Abstract : BACKGROUND: Four similar transfusion reactions involving infants were reported in less than 1 year. After transfusion of red blood cells (RBCs) via syringe in the operating room, each patient experienced discolored urine, laboratory evidence of hemolysis, and acute kidney injury. Clerical and serologic investigations were unremarkable. Mechanical hemolysis was considered. STUDY DESIGN AND METHODS: Simulated syringe transfusions were performed. Measurements included hematocrit (Hct), free hemoglobin, and visual hemolysis index. Washed and unwashed RBCs were tested with or without a recently introduced one‐way valve, using a 24‐ or 16‐gauge intravenous catheter. Constant manual pressure (1.43 ± 0.49 mL/sec) or syringe pump (2 mL/min) was used and a subset was timed. RESULTS: The valve increased hemolysis during manual transfusion using both catheters with washed and unwashed RBCs. With the 24‐gauge catheter, the change in Hct was –3.53 ± 0.69% with the valve and 0.22 ± 0.13% without (p < 0.00001). Comparing the individual valves tested, differences in hemolysis were observed (change in Hct, p < 0.0001). During manual transfusion with 24‐gauge catheter and unwashed RBCs, the degree of hemolysis was greater when it took longer to transfuse with a valve (change in Hct versus time, r = –0.75, p < 0.0001) compared to a slight increase in hemolysis for samples that took less time to transfuse without a valve (change in Hct versus time, r = 0.58, p = 0.23). CONCLUSIONS: Mechanical hemolysis should be considered when investigating possible hemolytic transfusion reactions, especially with high rates of transfusion and use of a valve. During rapid manual transfusion with the valve, greater resistance was associated with increased hemolysis.